2016
DOI: 10.1371/journal.pone.0164483
|View full text |Cite
|
Sign up to set email alerts
|

Living at Higher Altitude and Incidence of Overweight/Obesity: Prospective Analysis of the SUN Cohort

Abstract: BackgroundResidence at high altitude has been associated with lower obesity rates probably due to hypoxia conditions. However, there is no evidence of this association in a free-living population.ObjectivesWe assessed the association between the altitude where each participant of a Spanish cohort (the SUN Project) was living and the incidence of overweight/obesity.MethodsThe SUN Project is a dynamic, prospective, multipurpose cohort of Spanish university graduates with a retention rate of 89%. We included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
1
31
1
1
Order By: Relevance
“…Aging induces deterioration of various physiological functions, such as the decrease of muscle, pulmonary and cardiovascular functions, resulting in limiting physical activity . In addition, this issue also involves an increased obesity rate as a result of decreases in energy metabolism, metabolic hormone and muscle mass . Obesity in the older adult population has negative synergetic effects, leading to increased risk of premature mortality through various clinical diseases, such as metabolic syndrome, diabetes, cardiovascular diseases and musculoskeletal disorders .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging induces deterioration of various physiological functions, such as the decrease of muscle, pulmonary and cardiovascular functions, resulting in limiting physical activity . In addition, this issue also involves an increased obesity rate as a result of decreases in energy metabolism, metabolic hormone and muscle mass . Obesity in the older adult population has negative synergetic effects, leading to increased risk of premature mortality through various clinical diseases, such as metabolic syndrome, diabetes, cardiovascular diseases and musculoskeletal disorders .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In addition, this issue also involves an increased obesity rate as a result of decreases in energy metabolism, metabolic hormone and muscle mass. 4,5 Obesity in the older adult population has negative synergetic effects, leading to increased risk of premature mortality through various clinical diseases, such as metabolic syndrome, diabetes, cardiovascular diseases and musculoskeletal disorders. [6][7][8] Therefore, various studies on anti-aging and anti-obesity are crucial in reducing the mortality rate through health promotion of the older adult population.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 However, it has been speculated that modest differences in altitude might play a role in human health. 37 For example, it has been reported that obesity and diabetes are less prevalent [38][39][40] and that patients with coronary heart disease would live longer in areas under 1.5-km elevation. 41 Animal experiments employing a simulated altitude of about 1370 m (4500 ft) also supported that consistent mild hypobaric hypoxia will produce changes in behavior and antidepressant responses.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was significantly higher at lower altitude category (<500 m) in an US cross-sectional study after controlling for urbanization, temperature, behavioral and demographic factors (males and females had 5.1 and 3.9 times the odds of obesity, respectively, compared to participants over 3000 m) (Voss et al, 2013). A study about the incidence of overweight/obesity at geographical altitude performed in the SUN cohort found a reduction in the risk of developing overweight or obesity (Diaz-Gutierrez et al, 2016). Lately, a quasi-experimental study carried out with military population observed that individuals with frequent migration stationed at high altitude had 41% lower HR of obesity after multiple adjustment (Voss et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning modifiable factors, the environment has been suggested to potentially influence the development of metabolic diseases (Friel et al, 2011; Dhurandhar and Keith, 2014; Valdes et al, 2014). Moreover, some studies on subjects living at high altitudes have reported lower incidence rates of conditions linked to MetS such as obesity (Voss et al, 2013; Woolcott et al, 2014; Diaz-Gutierrez et al, 2016), heart disease (Ezzati et al, 2012; Faeh et al, 2016), hypertension (Norboo et al, 2015) or type 2 diabetes (Woolcott et al, 2014). …”
Section: Introductionmentioning
confidence: 99%